Pengaruh Pemasaran Media Sosial dan Store Atmosphere Terhadap Minat Beli Pelanggan di Kedai Kopi Bertema Industrial Kota Palembang - Angel, Alycia; Wijaya, Quincy Riani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is related to examining the phenomenon of the influence of social media marketing and Store Atmosphere in coffee shops on consumer buying interest by applying quantitative methods that are causal in nature. The population determined in this research is coffee shop visitors. The sample determined in this research used a non-random and purposive sampling method, where if determined specifically, the criteria were: domiciled in Palembang, have social media, have an interest in coffee shops and have visited coffee shops. Multiple linear regression analysis using SPSS is used in this research as a tool for processing and testing data. The results of this research show that the social media marketing variable has an effect on buying interest, while the store atmosphere variable has no effect on buying interest